Role of serum myeloperoxidase, CPK, CK-MB, and cTnI tests in early diagnosis of myocardial ischemia during ERCP - Yıldız, Kemal; Tüzün İnce, Ali and Sarbay Kemik, Ahu and Sert, Selin and İsen, Hayati Can and Tozlu, Mukaddes and Baysal, Birol and Akyüz, Ümit and Kocaman, Orhan and Danalıoğlu, Ahmet (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Some patients may experience retrosternal pain during ERCP, which may be a pioneer of a serious myocardial problem, and early diagnosis is very important for the prognosis and management. In the study, we aimed to investigate the role of serum cardiac biomarkers, such as myeloperoxidase (MPO), creatine phospokinase (CPK), creatine kinase- myocardial band (CK-MB), and cTnI, on early diagnosis of myocardial ischemia during endoscopic retrograde cholangio pancreaticograpy (ERCP) procedures. Materials and Methods: In this prospective observational study, ERCP patients were separated into ischemic cardiac (n:48) and non-ischemic (n:76) groups. Serious cardiac, kidney, and liver disease patients were excluded from the study. Changes in electrocardigrapy (ECG), blood pressure, pulse rate, oxygen saturation, and serum MPO, CPK, CK-MB, and cTnI levels were investigated before and after the ERCP. Results were evaluated statistically (p<0.05). Results: Mean age was 59.76±16.62 (55♀, 69♂). Only one patient had clinically unimportant retrosternal pain (0.8%). ST-elevation was detected in 10.4% (n:5), ST-depression in 12.5% (n:6), and negative-T in 31.3% (n:15) of ischemic patients during ERCP. Systolic and diastolic blood pressure and pulse rates in both groups and oxygen saturations in the ischemic group were reduced after ERCP. Significance was not detected with MPO and CPK tests. CK-MB levels showed an increase after the ERCP in the non-ischemic group (p<0.001). cTnI means were higher among the ischemics when pre- and post-ERCP periods (p:0.001) were compared. Conclusion: Clinically unimportant retrosternal pain, T negativity, and ST segment changes as well as reduced systolic, diastolic blood pressure, and heart rates can be seen during ERCP. MPO and CPK levels remain insignificant if myocardial injury does not develop. Increased CK-MB levels in non-ischemic patients and increased cTnI levels in ischemics may be seen.